Gastric serosal tear due to congenital pyloric atresia: A rare anomaly, a rare complication - Mithat Gunaydin; Rizalar Rizalar; Asudan Tugçe Bozkurter; Burak Tander; Ender Ariturk; Ferit Bernay (Wolters Kluwer Medknow Publications, 2011)
Congenital pyloric atresia (CPA) is a very rare malformation with unknown aetiology. It has has numerous complications including gastric perforation, aspiration pneumonia. Gastric perforations in newborns occur by three mechanisms: trauma, ischaemia, or spontaneous. Here, we report a newborn with CPA presenting with gastric serosal tearing without full-cut gastric perforation. The diagnosis was confirmed with the help of plain abdominal radiograph, ultrasound, contrast-study, and at operation. Treatment of CPA is surgery irrespective of the type of atresia. We performed serosa repair and then the solid, cord-like atretic pylorus was excised with accompanying gastroduodenostomy. Our patient had an uneventful course and was discharged at the end of the second postoperative week.